Teaching Bulacan delicacy preparation to adolescents with mental retardation - Arambulo, Arqueen (2008)
This study evaluated the performance of adolescents with mild to moderate mental retardation in the preparation of Bulacan delicacies using a research-designed instructional module, task analysis, and realia administered to eight adolescents. Results showed that adolescents with mental retardation could be trained to prepare the said delicacies using task analysis, verbal prompts, and realia. Depending on the complexity of procedures, some need assistance but the majority was able to work on their own. SPED facilitators should know how to manage the varying behaviors of adolescents with mental retardation in order to maximize their potentials.